Spaces for Mindfulness: Interiors that foster meditation and inner peace - Wajeeha Fatima; Deepti Pande Rana (International Journal of Architectural Design and Planning, 2025)
This dissertation explores the role of interior design in fostering mindfulness, meditation, and internal peace through thoughtfully designed spaces. The research investigates how various design elements—together with lighting fixtures, color schemes, spatial arrangement, acoustics, and material selection—can create environments that sell relaxation, intellectual readability, and emotional nicely-being. Central to the have a look at is the exploration of how mindful layout can beautify occupant comfort and psychological well-being with the aid of developing tranquil and balanced spaces that encourage meditation practices. The dissertation emphasizes the significance of integrating biophilic design ideas, which includes the inclusion of herbal elements and greenery, to enhance the indoor surroundings and beef up the connection to nature. Additionally, the studies examine how cultural context affects the layout of mindfulness areas, especially inside the context of Eastern and Western techniques to meditation and spirituality. The take a look at also address the role of herbal mild, sound management, and spatial waft in fostering a experience of calm and presence, that are key additives for meditation and mindfulness. Moreover, the dissertation investigates how these layout elements no longer most effectively contribute to mental health and relaxation however additionally to the overall properly-being of occupants. Finally, the dissertation appears ahead to destiny design tendencies and technology which can further decorate the development of spaces that help mindfulness and internal peace.
Keywords: Biophilic Design; Green architecture; Sustainable luxury; eco-friendly interiors; energy efficiency